2016
DOI: 10.1016/j.jpsychires.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Problem-gambling severity and psychiatric disorders among American-Indian/Alaska native adults

Abstract: Introduction Little is known about the association between problem-gambling severity and psychiatric disorders among American-Indian/Alaska-Native (AI/AN) individuals. Thus, we examined these factors among a nationally representative sample of AI/AN and other American adults in the USA. Method Using the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) data, we conducted separate Wald tests and multinomial logistic regression analyses comparing AI/AN to black/African American, white/Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Further analyses by age among individuals with subclinical pathological gambling revealed that more men were in the 18-to 29-year age group, while more women were in the 65 years or more age group. Stronger associations between pathological gambling and psychiatric disordersmood, anxiety and personality disorderswere evident among women as compared with men (Petry et al, 2005), and among American Indian/Alaskan Native adults (Kong et al, 2016). Problem/pathological gambling prevalence rates were 0.70% among men and 0.40% among women (Desai & Potenza, 2008).…”
Section: Sociodemographics and Potential Risk Factorsmentioning
confidence: 89%
See 1 more Smart Citation
“…Further analyses by age among individuals with subclinical pathological gambling revealed that more men were in the 18-to 29-year age group, while more women were in the 65 years or more age group. Stronger associations between pathological gambling and psychiatric disordersmood, anxiety and personality disorderswere evident among women as compared with men (Petry et al, 2005), and among American Indian/Alaskan Native adults (Kong et al, 2016). Problem/pathological gambling prevalence rates were 0.70% among men and 0.40% among women (Desai & Potenza, 2008).…”
Section: Sociodemographics and Potential Risk Factorsmentioning
confidence: 89%
“…Racial comparisons based on a sample of 32,316 White and Black adults revealed that problem/pathological gambling rates were higher for Black (0.96%) than White (0.45%) individuals (Barry et al, 2011a). American Indian/Alaskan Native as compared with other Americans (using the total 43,093 Wave 1 sample) were least likely to report non-/low-frequency gambling (American Indian/Alaskan Native: 66.5%, White: 70.5%, Black: 72.8%, and other race: 72.3%) and most likely to report low-risk gambling (American Indian/Alaskan Native: 30.1%, White: 26.5%, Black: 23.4%, and other race: 24.7%; Kong et al, 2016). It is important to note that percentages vary according to specified sample parameters of each study based on the NESARC data.…”
Section: Sociodemographics and Potential Risk Factorsmentioning
confidence: 99%
“…Other studies have pointed to the associations among abuse, mental health problems, and gambling addictions [ 93 , 94 ]. A study with survivors of child sexual abuse in residential schooling found that survivors had unresolved grief, and that was linked to pathological gambling [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study with survivors of child sexual abuse in residential schooling found that survivors had unresolved grief, and that was linked to pathological gambling [ 93 ]. Another study found a strong association between problem gambling and past-year psychiatric disorders among AIAN compared to non-AIANs [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…A dose response, biological gradient, was found in that as the number of gambling problems increased so did the likelihood of meeting the criteria for a personality disorder [10]. In another study utilizing data from NESARC, Kong and colleagues examined the association between problem gambling and comorbid psychiatric disorders among American-Indian/Alaskan Natives (AI/AN) in the US [11**]. Compared to Caucasians and African Americans, AI/AN were more likely to be non- gamblers or infrequent gamblers and were most likely to report in low-risk gambling.…”
Section: Comorbiditymentioning
confidence: 99%